Blockchain implementation in smart cities: Discussion on performance indicators - Ivanišević, Stojan; Ivić, Aleksandar; Ćirić, Zoran (Strategic management (Online), 2023)
Background: Blockchain project implementation in smart cities represents a novel challenge in information technologies. Lack of functional framework and guidelines impact these implementations and add additional uncertainty. Authors in their research on this subject seek to discover a functional framework to improve the implementation process. The research is divided into 3 parts: identification of best application areas, critical success factors, and implementation performance indicators. Purpose: The goal of this paper is to present findings on the performance indicators and offer additional insight into their nature as well as point to lesser-known performance indicators of blockchain projects. Study design/methodology/approach: Authors used the Delphi technique and according to the methodology, a panel of 33 experts was presented with a list of performance indicators and asked to add additional performance indicators as well as to assess their importance. The research foundation was based on the literature review which resulted in 9 performance indicators for the blockchain project implementation in smart cities. Findings/conclusions: The experts proposed 8 additional performance indicators; however, only 1 of them had required consensus to be accepted by the panel. This paper will disclose both groups of performance indicators and preserve them for further scientific discussion since the performance indicators that were proposed by the individual experts but did not reach panel consensus will not be contained in the further research results. After all rounds of the Delphi method were finished the experts concluded the list of the 5 most important performance indicators for the implementation of blockchain projects in the smart city. Limitations/future research: Due to limited resources and lack of experts, the size of the panel is limited to only 33 experts. In addition, smart cities are usually managed by the public sector, so access to all data is limited. The findings presented in the paper can be further used to improve the efficiency of blockchain projects.